A class of the NSVZ renormalization schemes for N=1 SQED - I.O. Goriachuk; A.L. Kataev; K.V. Stepanyantz (Physics Letters B, 2018)
For the N=1 supersymmetric electrodynamics we investigate renormalization schemes in which the NSVZ equation relating the β-function to the anomalous dimension of the matter superfields is valid in all loops. We demonstrate that there is an infinite set of such schemes. They are related by finite renormalizations which form a group and are parameterized by one finite function and one arbitrary constant. This implies that the NSVZ β-function remains unbroken if the finite renormalization of the coupling constant is related to the finite renormalization of the matter superfields by a special equation derived in this paper. The arbitrary constant corresponds to the arbitrariness of choosing the renormalization point. The results are illustrated by explicit calculations in the three-loop approximation.